Effects of cold-water immersion on health and wellbeing: A systematic review and meta-analysis. - Tara Cain; Jacinta Brinsley; Hunter Bennett; Max Nelson; Carol Maher; Ben Singh (PLoS ONE)
Background Cold-water immersion (CWI) has gained popularity as a health and wellbeing intervention among the general population. Objective This systematic review and meta-analysis aimed to evaluate the psychological, cognitive, and physiological effects of CWI in healthy adults. Methods Electronic databases were searched for randomized trials involving healthy adults aged ≥ 18 years undergoing acute or long-term CWI exposure via cold shower, ice bath, or plunge with water temperature ≤15°C for at least 30 seconds. Outcomes of interest were sleep, stress, fatigue, energy, skin health, immunity, inflammation, mental wellbeing, depression, anxiety, mood, concentration, and alertness or focus. Meta-analyses were conducted using RevMan software (version 5.4), applying random effects models to calculate standardized mean differences (SMD) between pre- and post-CWI exposure outcomes. Risk of bias was assessed using the PEDro scale. Results Eleven studies were included, comprising 3177 total participants and a mean PEDro score of 6.4 (n = 7 moderate quality, n = 4 high quality). CWI interventions were performed in baths (n = 10) or showers (n = 1) at temperatures ranging from 7°C to 15°C and durations ranging from 30 seconds to 2 hours. The meta-analysis revealed significant increases in inflammation immediately (SMD: 1.03, [95% CI: 0.37, 1.68], p <  0.01) and 1 hour post CWI (SMD: 1.26, [95% CI: 0.59, 1.94], p <  0.01), indicating an acute inflammatory response. A significant reduction in stress was observed 12 hours post-CWI (SMD: -1.00, [95% CI: -1.40, -0.61], p <  0.01), however, no significant effects on stress were detected immediately (SMD: -0.09 [95% CI: -0.45, 0.63], p >  0.05), 1 hour (SMD: -0.29 [95% CI: -0.66, 0.08], p >  0.05), 24 hours (SMD: -0.06 [95% CI: -0.50, 0.38], p >  0.05), or 48 hours (SMD: 0.09 [95% CI: -0.28, 0.46], p >  0.05) post-exposure. While meta-analysis showed no significant effects on immune function immediately (SMD: -0.16 [95% CI: -0.82, 0.51], p >  0.05) or 1 hour (SMD: -0.18 [95% CI: -1.09, 0.74], p >  0.05) post-CWI, narrative synthesis suggested longer-term benefits, including a 29% reduction in sickness absence among participants who took cold showers. Improvements were also observed in sleep quality and quality of life, but not mood. Conclusions This systematic review suggests that CWI delivers time-dependent effects on inflammation, stress, immunity, sleep quality, and quality of life, offering potential practical applications for health practitioners considering CWI for stress management and wellbeing support. However, the current evidence base is constrained by few RCTs, small sample sizes, and a lack of diversity in study populations. Future high-quality RCTs are needed to examine the long-term effects of CWI, its impact on diverse health outcomes, and optimal CWI protocols. PROSPERO (ID: CRD42024500591).